Термодинамiчна теорiя збурень для класичних систем в наближеннi самоузгодженого поля - Poluektov, Yu. M. (Publishing house "Academperiodika", 2019)
A formulation of the thermodynamic perturbation theory for classical many-particle systems, which is based on a self-consistent field model as the main approximation, has been proposed. Systems of particles in a spatially homogeneous state and in external fields that increase or decrease as the distance from the surface changes are considered as an example. The application of the self-consistent field approach as the main approximation is found to enable the description of many-particle systems, in which the concentration of particles and the interactions between them are not low, as well as phase transitions in such systems.